CURRICULUM DEVELOPMENT: THEORIES, PRINCIPLES, AND MODELS IN EDUCATION - Sri Mirnawati; Muhammad Febri Mawardi; Edi Fakhrin; Widy Noviani; Aulia Safitri; Suhaimi; Muhammad Saleh (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to describe the application of humanistic theory in the development of the Independent Curriculum (Kurikulum Merdeka) at SMP Negeri 2 Martapura. The research employs a qualitative case study approach with data collected through interviews, observations, and document analysis. Findings show that the humanistic theory serves as the main foundation for curriculum development, where teachers act as facilitators and students as the center of learning. The curriculum model combines top-down and bottom-up approaches, creating a flexible and contextually relevant framework. Implementation is carried out through active, collaborative, and reflective learning methods such as Project-Based Learning and Discovery Learning. Curriculum evaluation is conducted reflectively and continuously, involving teachers, school leaders, and the school committee. The application of humanistic principles has enhanced student motivation, independence, and character formation. The study recommends strengthening teacher professionalism and continuous collaboration between schools and communities to support the success of Independent Curriculum (Kurikulum Merdeka)